The social significance of dining out : a study of continuity and change - Warde, Alan; Paddock, Jessica; Whillans, Jennifer (Manchester University Press, 2020)
The book reports on a major research project on changes in dining out in three cities in England. It compares systematically popular practice in 1995 and 2015. Differences in taste and behaviour surrounding eating in restaurants and as guests of friends are put in the context of wider social and cultural trends.